TRAINING IN READING THE QUR'AN USING THE TAHSIN METHOD IN THE MAGHRIB MENGAJI ACCELERATION PROGRAM - hasnah nur (Journal of Humanity Dedication, 2023)
Teaching and learning activities about understanding the method of Qur'an Reading Training with Tahsin Method TPQ Al Falah Nagari Pauh Kambar, Padang Pariaman students at the Ibtidaiyah (SD / MI) and Tsanawiyah (SMP / MTs) levels in Pauh Kambar Padang Pariaman. At this level the motivation to learn the Koran in children is very minimal because of the lack of ability to read the Koran. The purpose of this teaching and learning activity is to increase children's learning motivation to be fluent in reading the Koran. The method used in this service activity is a descriptive model with a lecture, discussion, and question and answer approach and simulation. The results of teaching and learning activities include: First, students better understand the theory of tajweed. Second, they are motivated to learn the Koran better. Third, with the tahsin method, students can easily improve or improve their reading. Fourth, there are significant changes after using the tahsin method. Fourth, getting an enthusiastic response from teachers and students and has also been well implemented. Keywords: Qur'an Reading Training, Tahsin Method, Mahgrib Mengaji